2021
DOI: 10.1186/s12889-021-11755-z
|View full text |Cite
|
Sign up to set email alerts
|

Older patients’ perspectives on factors contributing to frequent visits to the emergency department: a qualitative interview study

Abstract: Background Older patients are at high risk of unplanned revisits to the emergency department (ED) because of their medical complexity. To reduce the number of ED visits, we need more knowledge about the patient-level, environmental, and healthcare factors involved. The aim of this study was to describe older patients’ perspectives and experiences before and after an ED visit, and to identify factors that possibly contribute to frequent ED revisits. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(46 citation statements)
references
References 55 publications
3
43
0
Order By: Relevance
“…Our work builds upon the extant literature by elucidating salient and generalizable barriers experienced by older adults experiencing ED‐to‐community care transitions. Prior qualitative research has relied on staff perceptions of older adults, 30 focused on modifiable reasons for ED utilization rather than ED‐to‐community care transitions, 31 or assessed the implementation of a specific program targeting a specific population 32 . Furthermore, prior research has identified barriers to successful ED‐to‐community care transitions across all ages, 33 with emphasis placed specifically on follow‐up compliance, ED navigators, and telephone calls, and the last being similarly called upon by older adults in this work.…”
Section: Discussionmentioning
confidence: 99%
“…Our work builds upon the extant literature by elucidating salient and generalizable barriers experienced by older adults experiencing ED‐to‐community care transitions. Prior qualitative research has relied on staff perceptions of older adults, 30 focused on modifiable reasons for ED utilization rather than ED‐to‐community care transitions, 31 or assessed the implementation of a specific program targeting a specific population 32 . Furthermore, prior research has identified barriers to successful ED‐to‐community care transitions across all ages, 33 with emphasis placed specifically on follow‐up compliance, ED navigators, and telephone calls, and the last being similarly called upon by older adults in this work.…”
Section: Discussionmentioning
confidence: 99%
“…It was probably my own insecurity, I was confused, and I just did not remember things well. That was really disturbing and worrying” [ 32 ].…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
“…I do not see any progression in my recovery and I expected that. Because, until now...so far things are not so positive” [ 32 ].…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
“…This is reflected in the hospitalization, return rates, and deaths in older adults compared with those in younger patients. Approximately 10%–23% of older patients return unexpectedly within the first month, 14 ) and up to 25% of older adults return to the ED within 3 months. 11 ) Within 3 months of discharge, 12.4% of the older patients die, 18.3% are hospitalized, and 2.6% subsequently enter a nursing home.…”
Section: Introductionmentioning
confidence: 99%